The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1523/jneurosci.23-29-09595.2003
|View full text |Cite
|
Sign up to set email alerts
|

GLR-1, a Non-NMDA Glutamate Receptor Homolog, Is Critical for Long-Term Memory inCaenorhabditis elegans

Abstract: Long-term memory for habituation to tap in Caenorhabditis elegans depends on glr-1, a homolog of mammalian non-NMDA glutamate receptors; mutations in glr-1 blocked long-term memory formation. Green fluorescent protein (GFP) constructs were used to visualize glr-1 expression in the interneurons of the mechanosensory circuit and synaptobrevin in the tap sensory neurons of trained and untrained worms. Trained animals had less GLR-1::GFP expression than untrained animals; there was no difference in the vesicle mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
133
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(139 citation statements)
references
References 23 publications
5
133
0
Order By: Relevance
“…eat-4 mutants display faster than normal habituation of responses to plate-tap at all ISIs, slower spontaneous recovery, and an inability to produce LTM [62,64]. Meanwhile, glr-1 encodes a non-NMDA glutamate receptor expressed in all four interneurons (AVA, AVB, AVD, and PVC) that synapse with the touch receptor neurons, and mutations in glr-1 also block LTM of habituation [63]. It is interesting to note that tap training of C. elegans modifies the density of postsynapse GLR-1 of the interneurons [63,66].…”
Section: Habituationmentioning
confidence: 99%
See 1 more Smart Citation
“…eat-4 mutants display faster than normal habituation of responses to plate-tap at all ISIs, slower spontaneous recovery, and an inability to produce LTM [62,64]. Meanwhile, glr-1 encodes a non-NMDA glutamate receptor expressed in all four interneurons (AVA, AVB, AVD, and PVC) that synapse with the touch receptor neurons, and mutations in glr-1 also block LTM of habituation [63]. It is interesting to note that tap training of C. elegans modifies the density of postsynapse GLR-1 of the interneurons [63,66].…”
Section: Habituationmentioning
confidence: 99%
“…Meanwhile, glr-1 encodes a non-NMDA glutamate receptor expressed in all four interneurons (AVA, AVB, AVD, and PVC) that synapse with the touch receptor neurons, and mutations in glr-1 also block LTM of habituation [63]. It is interesting to note that tap training of C. elegans modifies the density of postsynapse GLR-1 of the interneurons [63,66]. These results suggest that glutamatergic transmission from the touch neuron to interneuron plays an important role in habituation.…”
Section: Habituationmentioning
confidence: 99%
“…A wealth of knowledge has been obtained about the underlying mechanisms of learning and memory, but much remains to be elucidated. Previous studies have revealed regulators of learning and memory conserved between mammals and Caenorhabditis elegans (1)(2)(3)(4)(5)(6)(7). Therefore, the analysis of genes found in C. elegans can provide important insights into the mechanisms of learning and memory in mammals, including humans.…”
mentioning
confidence: 99%
“…That is, when a strong enough stimulus is used for training, it may lead to sufficient glutamate release, and result in long-term memory. The hypothesis that glutamate transmission is required for long-term memory formation is further supported by the study from Rose et al (2003). Mutation of glr-1 caused no long-term memory for distributed training regardless of whether a tap or a train of taps was used as the habituation training stimulus [23] .…”
Section: Intermediate Memory For Habituationmentioning
confidence: 91%
“…The hypothesis that glutamate transmission is required for long-term memory formation is further supported by the study from Rose et al (2003). Mutation of glr-1 caused no long-term memory for distributed training regardless of whether a tap or a train of taps was used as the habituation training stimulus [23] . Trained animals had less GLR-1::GFP expression than untrained animals [23] .…”
mentioning
confidence: 91%